ftsI mutations versus beta-lactamase (blaTEM) production in beta-lactam resistance of Haemophilus influenzae: results from an university hospital in Istanbul - Meltem Sarı Küçükerol; Burak Aksu; Ufuk Hasdemir (Journal of Global Antimicrobial Resistance)
AIM: To determine in vitro susceptibilities of H. influenzae strains and to reveal the beta-lactam resistance mechanisms involved in those resistant to beta-lactams in our center. METHODS: Antibiotic susceptibilities of 122 H. influenzae isolated in 2022 were determined by disk diffusion method (DDm). The presence of β-lactamase was investigated phenotypically (Cefinase-test, BD, USA) and genotypically (blaTEM, blaROB) by PCR in isolates found positive in benzyl-penicillin-screening test (BPT) in DDm. In BPT-positive isolates, the ftsI gene was amplified by PCR and products were sent to Eurofins-Genomic Lab. (Germany) for sequencing. The results were analysed for mutations associated with beta-lactam resistance by comparing them with the sequence of reference H. influenzae Rd KW20 available in the database http://blast.ncbi.nlm.nih.gov/Blast.cgi. RESULTS: BPT was positive in 57 (46.7%) of 122 isolates (Table 1). Beta-lactamase was detected both phenotypically and/or genotypically in 15 of 57 isolates. No resistance was found in any isolate to ceftriaxone and carbapenems. Of the 57 BPT-positive isolates, 51 (excluding 6 β-lactamase positive amoxicillin/clavulanic-acid susceptible isolates) were sent for ftsI sequencing (Table 2). N526K mutation associated with low-level beta-lactam resistance were detected in 41 isolates (group II) and S385T mutation associated with high-level beta-lactam resistance in 4 isolates (group III-like/group III+). CONCLUSIONS: - Almost half of the isolates (46.7%) were resistant to at least one beta-lactam- No resistance to ceftriaxone and carbapenems- Low rate (12.3%) of beta-lactamase production- High rate (36.9%) of isolates with ftsI mutations- Prevalence of the isolates with low-level beta-lactam resistance (group II)